THE EFFECT OF WORKLOAD AND COMMUNICATION ON EMPLOYEE WORK PERFORMANCE AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF BIMA CITY - Ningsi, Anggil; Kusumayadi, Firmansyah; Amar, Khairul (Universitas Putera Batam, 2025)
The purpose of this study is to determine the effect of Workload and communication on employee performance at the Population and Civil Registration Office of Bima City. The type of research that will be used in this study is Associative research using quantitative data from primary data sources. The instrument in this study used a Likert scale questionnaire sheet with a population of 48 employees consisting of 27 civil servants, 3 PPPK, 14 Regional Honorary employees and 4 voluntary honorary employees. The sample in the study was 30 employees at the Population and Civil Registration Office of Bima City consisting of 27 civil servants and 3 PPPK. The sampling technique was carried out using the purposive sampling method. Data in this research were collected by means of observation, interviews, questionnaires and literature study, then the data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, multiple correlation coefficients, determination tests, t tests and f tests with SPSS version 26 help. The results of the study show that employee workload and employee work communication have a significant effect on employee work performance at the Population and Civil Registration Service of Bima City.